The Bumiputera Policy and "Dayakism": An Interpretation - Richard Mason,; Jayum A. Jawan, (Kajian Malaysia, 2003)
The cry of "Dayakism" in Sarawak politic has somewhat receded over the past decade but during the 1980s through the early 1990s, it was a popular, even fashionable, political slogan among its proponents- The word, of course, comes from the root-word "Dayak," which is a collective reference for the non-Muslim indigenous groups in Sarawak. When "ism" is added as a suffix, however, it assumes a whole complexity of meanings. It is often assumed that by adding "ism" to such a word, the word is then transformed to describe an ideology or a phenomenon, much like the word "nationalism".